Pertunjukan Kesenian dalam Rangkaian Pesta Pernikahan di Kecamatan Pondok Tinggi Kota Sungai Penuh Provinsi Jambi - Fitri Rahayu; Fuji Astuti (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
The purpose of the study is to describe Art Performances in a Series of Wedding Parties in Pondok Tinggi District, Sungai TFull City, Jambi Province. The type of research used is qualitative research with the method used is descriptive analysis. The object of this study is Art in a series of wedding parties, namely art activities in the form of joyful performances of Rentak Kudo. The research instruments or tools are the researchers themselves and are assisted by supporting instruments such as smartphone cameras, voice recorders and flash disks. The data collection techniques used are literature studies, direct observation, interviews, and documentation. The steps taken by the researcher in analyzing the data are data reduction, data display, and drawing conclusions. The results of the study show that the Art Performance at the Wedding Party is described in accordance with the conceptual framework which includes: 1) The relationship between the community of Sungai TFull City and the art performance at the wedding. 2) The relationship between the meaning of art performances based on textual, which consists of movement, expression, floor patterns, dancers, costumes, music, makeup, and performance venues with contextual, namely consisting of wedding parties, wedding processions and social values